Inter-laboratory studies for the validation of two singleplex (tE9 and pea lectin) and one duplex (pat/bar) real-time PCR methods for GMO detection. (March 2017) - Debode, F.; Huber, I.; Macarthur, R.; Rischitor, P.E.; Mazzara, M.; Herau, V.; Sebah, D.; Dobnik, D.; Broeders, S.; Roosens, N.H.; Busch, U.; Berben, G.; et al.
Abstract: This paper presents the inter-laboratory studies for the successful validation of qualitative real-time Polymerase Chain Reaction methods for the detection of Genetically Modified Organisms in food and feed. Two singleplex TaqMan methods were developed for the detection of the tE9 terminator present in several genetically modified events and the detection of the endogenous lectin gene from pea; the tE9 terminator donor organism. In addition, a TaqMan duplex method was validated, which allows the simultaneous detection of the pat and bar elements. The paper explains the different acceptance parameters used during the in-house validation, the method transferability study and finally the inter-laboratory validation, how this validation was conducted and the problems encountered. Statistical methods for the validation of the qualitative methods are also presented. This information can be used by laboratories for the verification of these methods during their implementation and for the validation of new methods. Highlights: A new endogenous target for the detection of pea was developed. Singleplex and multiplex real-time PCR screening methods for GMO detection were validated. In-house validation, method transferability and inter-laboratory validation are described. Statistical approaches for the validation of qualitative methods are presented.